Design parameters optimization in CNC machining based on Taguchi, ANOVA, and screening method / Armansyah ... [et al.] - -, Armansyah; -, Lilik Zulaihah; Nasution, Siti Rohana; Sinaga, Gary Geraldus; Saedon, Juri (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2023)
Future manufacturing requires a process to achieve high productivity with high-quality products. Appropriate and optimum machining parameters during machining operation are essential to enhance the surface quality (Ra). This study investigated a design for machining parameter optimization to reduce time and cost with minimum experiments using the Taguchi method via the screening method. In this study, the machining parameters were the cut speed (vc), fed speed (vf), cut depth (doc), cut width (woc), and flute (z). The response analysed process was done on Aluminium alloy AA6061 via a high-speed computer numerical control machine (HSM) employing an end mill cutter in dry cutting. Analysis of Variance (ANOVA) of parameters combination applied during the process was used to analyse the results from data obtained and via the screening. Based on the result of ANOVA indicated that vf showed a greater F-value which meant vf had statistical significance for the terms and model. It was concluded that through the confirmation test, the optimal machining parameters vc at 220 rpm, vf at 150 mm/m, doc of 0.5 mm, woc at 4 mm, and z at 4 flutes, with Ra was around 0.122 - 0.127 which was achieved the requirement of standard for industries in polishing.